Empresários e intelectuais: agentes culturais e valorização de um grupo étnico - Maria Clara Mocellin (Ciências Sociais Unisinos)
The article aims to investigate an identity process of promotion of an ethnic group by focusing in the 1970s and 1980s, since this period is characterized by a process of mod- ernization of the economy in the region of Caxias Sul, in Rio Grande do Sul State. In order to explain this process of valuing the local culture, which is here called valuing italianity, the research project focuses on two groups, viz. intellectuals and entrepreneurs, since they are considered important social actors in the production of ethnical symbols. The research data showed close relations between entrepreneurs and intellectuals, established as they got together to implement strategies for regional development and to promote the local culture. The paper highlights a specific process of association of economic and intellectual capital, articulated though strategies of interest groups designed to legitimate and recognize a field of knowledge, as well as through actions designed to value and promote the local culture. In order to map the network of relations between these two groups, the article discusses trajectories of entrepreneurs and intellectuals involved in the promotion of the local culture and in regional development.